The use of computed tomography for the study of archaeological coins. (April 2016) - Miles, James; Mavrogordato, Mark; Sinclair, Ian; Hinton, David; Boardman, Richard; Earl, Graeme
Abstract: Computed tomography enables non-destructive three-dimensional densitometric information of the internal structure and external geometry of many archaeological artefacts to be acquired. This paper uses work completed by the μ-VIS X-ray Imaging Centre at the University of Southampton to illustrate how computed tomography can be used to accurately record surface and sub-surface data of intact coin hoards contained within pots. An examination of coin placement, coin identification and segmentation and extraction of individual coins for use within a virtual environment are presented. Computed tomography used in this way will enable numismatists to identify otherwise hidden coins, and to visualise, share and archive coin data. Highlights: Data has a maximum resolution of 131.3 microns Virtual identification of 201 coins 50% of the coins analysed were identifiable before excavation Introduction of Virtual RTI led to the identification of coin inscriptions previously missed Aided conservation of coins when excavated